FAKTOR RISIKO SANITASI RUMAH TERJADINYA PENYAKIT ISPA DI DESA MODOPURO KABUPATEN MOJOKERTO TAHUN 2021 - inayatulillah inayatulillah; Pratiwi Hermiyanti; Ernita Sari (Jurnal Hygiene Sanitasi, 2021)
One of the risk factors for the transmission of ARI is the condition of home sanitation that does not meet health requirements. Based on data from the Modopuro Health Center in 2020 in Modopuro village, 301 people with ARI were found and the number of healthy homes that did not meet the requirements was 46%. The results of a preliminary study of 15 houses found as many as 60% of the houses with sanitation conditions that did not meet the requirements. The purpose of this study was to analyze the relationship between home sanitation conditions with the incidence of ARI. This type of research is descriptive analytic with aapproach case control. The variables used in this study are temperature, humidity, occupancy density, ventilation, lighting, floors, and walls. The sampling technique used is simple random sampling with a total sample of 152 samples with a control ratio of 1:1. The data obtained were analyzed using the Chi Square test. The results of this study found variables that did not meet health requirements, namely temperature 92.1%, humidity 53.9%, occupancy density 54.6%, ventilation 49.3%, lighting 45.4%, floor 3.3%, walls 26.3% and house sanitation 55.3%. Variables of air humidity (p = 0.023), occupancy density (p = 0.000), ventilation (p = 0.001), lighting (p = 0.006), floor (p = 0.023), walls (p = 0.000), and house sanitation (p = 0.000) associated with the incidence of ARI. Conclusions based on the results of the study there is a relationship between home sanitation and ARI. The community is advised to maintain the sanitary conditions of the house, such as opening windows in the morning and cleaning the house regularly.